2008
DOI: 10.1007/s11258-008-9526-7
|View full text |Cite
|
Sign up to set email alerts
|

Role of desert annuals in nutrient flow in arid area of Northwestern China: a nutrient reservoir and provider

Abstract: Previous studies have tested the ''vernal dam'' hypothesis of spring ephemeral herbs in hardwood forests. The desert annual is a component of the desert ecosystem that takes advantage of water resources and temperature conditions during the rainy season to rapidly complete its life cycle within several months. To understand the role desert annual/ephemeral plants play in nutrient flow, we studied vegetation cover, nitrogen content and litter production of annual plants and litter decomposition rate in plant co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 37 publications
(46 reference statements)
0
12
0
Order By: Relevance
“…Relationships between desert plants and environmental factors in the Minqin ODE have been extensively investigated. These studies revealed the following aspects: (1) the effects of H. ammodendron plantations on soil physical-chemical properties, soil microorganisms (Xi et al, 2015;Fan et al, 2016), spatial pattern, soil water, and water budget of N. tangutorum nebkhas (Qiu et al, 2015;Yang et al, 2015); (2) the relationships of climate changes with vegetation gradient characteristics, vegetation restoration, water use, and reproductive phenology (Du et al, 2010(Du et al, , 2011Ma et al, 2010;Chang et al, 2012;Zhu et al, 2013;Han et al, 2015); (3) the clonal population of Calligonum mongolicum and its relationship with environmental factors (Zhou et al, 2012); and (4) vegetation succession, niche, traits, and physiological responses of desert plants to groundwater (Peng et al, 2004;Yang et al, 2007;Shi et al, 2008;Wei et al, 2008), vegetation, and soil nutrients (Chen et al, 2007(Chen et al, , 2009. However, most of these studies investigated the relationships between individual environmental factors and plants on a relatively small scale.…”
Section: Introductionmentioning
confidence: 99%
“…Relationships between desert plants and environmental factors in the Minqin ODE have been extensively investigated. These studies revealed the following aspects: (1) the effects of H. ammodendron plantations on soil physical-chemical properties, soil microorganisms (Xi et al, 2015;Fan et al, 2016), spatial pattern, soil water, and water budget of N. tangutorum nebkhas (Qiu et al, 2015;Yang et al, 2015); (2) the relationships of climate changes with vegetation gradient characteristics, vegetation restoration, water use, and reproductive phenology (Du et al, 2010(Du et al, , 2011Ma et al, 2010;Chang et al, 2012;Zhu et al, 2013;Han et al, 2015); (3) the clonal population of Calligonum mongolicum and its relationship with environmental factors (Zhou et al, 2012); and (4) vegetation succession, niche, traits, and physiological responses of desert plants to groundwater (Peng et al, 2004;Yang et al, 2007;Shi et al, 2008;Wei et al, 2008), vegetation, and soil nutrients (Chen et al, 2007(Chen et al, , 2009. However, most of these studies investigated the relationships between individual environmental factors and plants on a relatively small scale.…”
Section: Introductionmentioning
confidence: 99%
“…Ephemerals (with short life span), ephemeroids (perennial plants with short life span) and annuals (with longer life span than ephemeral and ephemeroid plants) are the three dominant plant life forms comprising the herbaceous layer in the Gurbantunggut Desert in northwestern China (Wang et al, 2003). These three types of plants usually account for more than 50% of the vegetation cover in early spring to summer and make a large contribution to the annual productivity of the desert vegetation in spring and autumn, and they also act as a nutrient reservoir for other plants (Chen et al, 2009;Huang et al, 2016). Ephemeral and ephemeroid plants both take advantage of the available water in a short period of time during the rainy season to complete their life cycle rapidly within a few months (Fan et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Among its sister species, only A. squarrosum is widely distributed in the mobile sand dunes of all deserts and sandy lands across the Asian interior ( http://foc.eflora.cn ) and can survive extremely high temperatures and drought and tolerate sand burial 17 18 19 . Because the withered plants reduce wind velocity by at least 90% and are a rich source of carbon and nitrogen in these poor soil environments, A. squarrosum plays a critical role in sustaining and restoring fragile desert ecosystems 20 21 . Furthermore, although this plant grows in infertile and sandy soils, A. squarrosum has a high concentration of nutrients in its seeds and a high biomass, thus making this plant an invaluable candidate species for domestication as a food and forage crop for dry lands 22 , More interestingly, the colonisation of A. squarrosum is often accompanied by the shifting of sand dunes, thus providing an ideal model to understand the historical dynamics of desert ecosystems in response to climate change.…”
mentioning
confidence: 99%